Pemetaan Literasi Lingkungan Siswa SMA dalam Pembelajaran Biologi Ditinjau dari Perbedaan Gender - Indah Sari, Tasya Novian; Riana Widiyanti, Eka (Program Studi S1 Pendidikan IPA, FMIPA Universitas Pendidikan Ganesha, 2024)
This study aimed to determine the effect of gender differences on the environmental literacy of high school students in East Oku Regency, South Sumatra, in biology learning. This study is an ex post facto associative study with a quantitative approach. The study was conducted in September-December 2023. The study Population was 8,832 high school students in grades X, XI, and XII of state and private schools in East Oku 2023. The research sample was 459 students using a simple random sampling technique. Data collection techniques using test and non-test techniques. The data collection instrument was a test with environmental literacy questions from the Middle Schools Environmental Literacy Survey and a non-test with a National Environmental Literacy Assessment questionnaire. Data analysis techniques using quantitative descriptive and the ann-Whitney test. The study results showed that students' environmental literacy abilities were moderate. There was no difference in ecological literacy abilities in the knowledge and behavior components. In contrast, in the attitude and cognitive skills components, there were differences in environmental literacy abilities between male and female students.